THE EFFECT OF ECONOMIC SUSTAINABILITY KPIs ON INVESTMENT PROFIT QUALITY AND FINANCIAL PERFORMANCE OF E-COMMERCE ISSUERS IN INDONESIA FOR THE PERIOD 2021–2024 - Reyza Diva Afiana; Mardi Mardi; Achmad Fauzi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the effect of economic sustainability indicators measured through Key Performance Indicators (KPIs) on investment earnings quality and financial performance among e-commerce issuers in Indonesia during the 2021 to 2024 period. The research employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that economic sustainability KPIs significantly influence investment earnings quality and financial performance. Earnings quality also significantly contributes to financial performance and partially mediates the relationship between economic sustainability KPIs and firm performance. These results emphasize the strategic importance of sustainability reporting in enhancing the quality of accounting information and improving long-term value creation in the digital sector.